Flash Card Learning Media to Improve Javanese Writing Skills in Elementary School - Candra, Purnomo Dwi; Hendratno, Hendratno; Sukartiningsih, Wahyu (Papanda Publisher, 2025)
This systematic literature review investigates the effectiveness of flashcard media in improving elementary students’ writing skills, specifically in learning Javanese script. By analyzing six peer-reviewed articles published between 2019 and 2024, this study synthesizes quantitative and qualitative findings related to flashcard interventions in primary school settings. The review reveals significant improvements in students’ reading and writing scores, enhanced motivation, and the successful integration of innovative learning models such as Make a Match and Modeling the Way. Expert validation confirmed the feasibility and cultural appropriateness of the developed media. Despite methodological variability across studies, consistent themes emerge around flashcard efficacy, motivational impacts, and skill development. The findings suggest that flashcards are an effective, low-cost, and engaging tool for local language literacy development. Recommendations for future research include longitudinal studies, expanded samples, and digital adaptations. This review contributes to educational practices aimed at revitalizing indigenous scripts and enhancing literacy skills in elementary education.